Effects of Sodium Thiosulfate During Resuscitation From Trauma-and-Hemorrhage in Cystathionine-γ-Lyase Knockout Mice With Diabetes Type 1 - Gröger, Michael; Hogg, Melanie; Abdelsalam, Essam; Kress, Sandra; Hoffmann, Andrea; Stahl, Bettina; Calzia, Enrico; Wachter, Ulrich; Vogt, Josef A.; Wang, Rui; Merz, Tamara; Radermacher, Peter; et al. (Frontiers in Medicine, 2022)
Background: Sodium thiosulfate (STS) is a recognized drug with antioxidant and H2S releasing properties. We recently showed that STS attenuated organ dysfunction and injury during resuscitation from trauma-and-hemorrhage in CSE-ko mice, confirming its previously described organ-protective and anti-inflammatory properties. The role of H2S in diabetes mellitus type 1 (DMT1) is controversial: genetic DMT1 impairs H2S biosynthesis, which has been referred to contribute to endothelial dysfunction and cardiomyopathy. In contrast, development and severity of hyperglycemia in streptozotocin(STZ)-induced DMT1 was attenuated in CSE-ko mice. Therefore, we tested the hypothesis whether STS would also exert organ-protective effects in CSE-ko mice with STZ-induced DMT1, similar to our findings in animals without underlying co-morbidity. Methods: Under short-term anesthesia with sevoflurane and analgesia with buprenorphine CSE-ko mice underwent DMT1-induction by single STZ injection (100 μg·g-1). Seven days later, animals underwent blast wave-induced blunt chest trauma and surgical instrumentation followed by 1 hour of hemorrhagic shock (MAP 35±5 mmHg). Resuscitation comprised re-transfusion of shed blood, lung-protective mechanical ventilation, fluid resuscitation and norepinephrine support together with either i.v. STS (0.45mg·g-1) or vehicle (n = 9 in each group). Lung mechanics, hemodynamics, gas exchange, acid–base status, stable isotope-based metabolism, and visceral organ function were assessed. Blood and organs were collected for analysis of cytokines, chemokines, and immunoblotting. Results: DMT1 was associated with more severe circulatory shock when compared to our previous study using the same experimental design in CSE-ko mice without co-morbidity. STS did not exert any beneficial therapeutic effect, and most of the parameters measured of the inflammatory response nor were the tissue expression of marker proteins of the stress response affected either. Conclusion: In contrast to our previous findings in CSE-ko mice without underlying co-morbidity, STS did not exert any beneficial therapeutic effect in mice with STZ-induced DMT1, possibly due to DMT1-related more severe circulatory shock. This result highlights the translational importance of both integrating standard ICU procedures and investigating underlying co-morbidity in animal models of shock research.